Memerangi Api dengan Api: Menggunakan Film untuk Melawan Film Propaganda - Gary Jason (PROPAGANDA, 2023)
His article explores how effective films are in countering propaganda in films. To organize the discussion, first a simple sketch of propaganda theory is drawn up, in which propaganda can be ranked from completely rational to highly irrational, on six different dimensions. This is how far the propaganda went: evidence-based; Honest; broadly logical; transparent; right on target; and transparent. Then the main propaganda film is reviewed in detail, Gasland. This film is a highly successful documentary attacking the production of natural gas by hydrofracturing, which is referred to in America as "fracking". Gasland was successful in organizing domestic opposition to fracking, actually blocking it in the Delaware River Basin system. The film was also influential abroad, leading to a ban on fracking in France, Bulgaria and elsewhere in Europe. Next, two counter-propaganda films are reviewed in detail—namely, in this case, two pro-fracking documentaries: Truthland and FrackNation. Truthland is a short documentary that refutes many of Gasland's important claims. It was funded by the fracking industry and had limited distribution but manage d to refute most of the longer, better-funded anti-fracking films. A much more successful film in terms of general distribution and debunking efficacy is the much longer pro-fracking documentary FrackNation. It critiques all Gasland's main points, in vivid detail. Due to crowdfunding, it cannot be ignored due to bias because it is supported by the industry. From this article it can be concluded by explaining why pro-fracking documentaries have not resulted in major changes in public opinion.